SOME TECHNOLOGICAL PROBLEMS OF CATALYTIC CONVERSION OF METHANE WITH CARBON DIOXIDE IN THE GAS PHASE WITH THE PARTICIPATION OF CATALYSTS - Koybakarob Oybek Ergashovich (Web of Journals Publishing, 2025)
As mentioned above, the industrial application of the catalytic conversion of methane in the gas phase with carbon dioxide catalysts is hindered by the fact that the process is highly exothermic., in other words, high energy consumption; secondly, very low stability of the catalyst to coking. The development of new catalysts continues as part of the fight against coking. We have already mentioned the work of the company "Topsoe" in the field of reducing the toxicity and coking of nickel catalysts [57; pp. 44-44].